Revision of the Theopea genus group (Coleoptera, Chrysomelidae, Galerucinae), part III: Descriptions of two new genera and nine new species - Lee, Chi-Feng (Zookeys, 2020)
Abstract. This publication treats species within Theopea and closely allied genera that were not covered in the previous two revisions. Three species of Theopea Baly, 1864 are treated herein, with T. bicolor Kimoto, 1989 and T. mouhoti Baly, 1864 redescribed, and T. bicoloroidessp. nov. described. A new genus that we consider closely related to Theopea, Pseudotheopeagen. nov., is described. This new genus can be recognized with the presence of reticulate microsculpture on the vertex of the head and pronotum and presence of an apical spine on each metatibia. The following species are transferred to Pseudotheopea as new combinations: Theopea aeneipennis Gressitt & Kimoto, 1963, T. azurea Gressitt & Kimoto, 1963, T. clypealis Medvedev, 2015, T. nigrita Medvedev, 2007, T. smaragdina Gressitt & Kimoto, 1963, T. similis Kimoto, 1989, and T. subviridis Medvedev, 2012. Theopea subviridis Medvedev, 2012 is regarded as new synonym of Pseudotheopea similis (Kimoto, 1989). In addition, six new species of Pseudotheopea are described: P. borerisp. nov. from India, P. gressittisp. nov. from Philippines, P. hsingtzungisp. nov. from Laos, P. kimotoisp. nov. from Laos, Thailand, and Vietnam, P. leehsuehaesp. nov. from Laos, and P. sufangaesp. nov. from Taiwan. A second new genus regarded as closely related to Pseudotheopea, Borneotheopeagen. nov., can be recognized by possessing uniform antennae in both sexes and lacking an apical spine on each metatibia. Two new species of Borneotheopea are described from Borneo: B. jaklisp. nov. and B. kalimantanensissp. nov.